(untitled) (Latakia University Journal -Medical Sciences Series, 2023)
Body image is an important issue for breast cancer patients, especially after they underwent surgery, so the current descriptive study aimed to evaluate the body image (Body Image BI) of 100 women in four hospitals in Lattakia and Tartous governorates during the early period after breast cancer surgeries, who were selected using the appropriate sampling method. The data was collected by means of a pre-prepared questionnaire for that, as the results showed that the BI was bad for the sample members, and the study found statistically significant differences due to the variable of the type of surgery, where the BI was worse for patients with bilateral (Mastectomy) M, and the BI was worse for patients with preparatory education or secondary, and their economic status is weak. The study recommended conducting further research to evaluate BI in particular in patients with M, and conducting future research to study the factors affecting BI at different time periods after surgery and to find appropriate interventions to improve it.